Organic food adoption motivations for sustainable consumption: moderating role of knowledge and perceived price - Kamran Khan; Sobia Iqbal; Kashif Riaz; Irfan Hameed (Cogent Business & Management, 2022)
The household spending of Pakistani consumers on sustainable food consumption has continued to remain low. Hence, the present study used the goal-framing theory to explore the consumer's motivational factors that derive sustainable consumption of organic food. Drawing on survey data of 488 respondents, the findings show that gain and hedonic motivations significantly affect purchase intentions; however, normative has an indirect role. In addition, the knowledge and perceived price significantly moderate the motivational factors. The study provides invaluable insights for policymakers and practitioners in identifying the motivational factors, and the means of guiding the right behaviors for sustainable consumption.
Keywords: 650; perceived price; sustainable food consumption; gain motivations; goal-framing theory; hedonic motivations